International commercial arbitration : international conventions, country reports and comparative analysis : a handbook - Balthasar, Stephan (London, England : Zed Books, 2020)
"Reviews from the first edition: 'This handbook deserves a place - near the writing desk of every lawyer practising in the field of international arbitration' Volker Triebel, Journal of International Arbitration 'This book should find its way to the bookshelves of internationally experienced arbitration lawyers' Christof Siefarth, Dispute Resolution This handbook provides an overview of the global framework of international commercial arbitration, in particular the New York Convention, the UNCITRAL Model Law, and international investment treaties. In addition, it offers comprehensive insight into international arbitration laws of countries covering over 60% of the global economy: Austria, Belgium, Brazil, China, England and Wales, France, Germany, Hong Kong, India, the Netherlands, Russia, Singapore, Spain, Sweden, Switzerland, and the US. The new edition includes numerous references to recent case law, material and legislative reform as well as topical developments in areas such as arbitrators' jurisdiction, the conduct of arbitral proceedings and the judicial control of arbitral awards."--
International Commercial Arbitration : Comparative Reflections on the UNCITRAL Model Law / Balthasar -- The New York Convention / Solomon -- Investment Treaty Arbitration / Wehland -- International Arbitration in Austria / Nueber/Zeiler -- International Arbitration in Belgium / Piers/Vanleenhove/De Meulemeester/Ongenae -- International Arbitration in Brazil / Lousa/Silva -- International Arbitration in China (People's Republic) / Wiegand/Ye -- International Arbitration in England and Wales / Illmer -- International Arbitration in France / Balthasar/Ziade -- International Arbitration in Germany / Balthasar -- International Arbitration in Hong Kong / Leung/Lo -- International Arbitration in India / Steinbruck -- International Arbitration in the Netherlands / Fasfalis/Krestin -- International Arbitration in the Russian Federation / Yuryev -- International Arbitration in Singapore / Selvaraj/Tan -- International Arbitration in Spain / Duncker -- International Arbitration in Sweden / Widjeskog -- International Arbitration in Switzerland / Richers/Magliana -- International Arbitration in the U.S. / Niedermaier.
Also published in print.
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily
Mode of access: World Wide Web.
Keywords: International commercial arbitration; Conflict of laws -- Arbitration and award; Law,Arbitration, mediation & alternative dispute resolution; Electronic books